National Strategic Project (Rempang EcoCity): Indigenous Peoples' Resistance in Responding to the Grabbing of Customary Land in Rempang Island - Aswad Asruddin, Fajar; Efendi , David (Journal of Law, Politic and Humanities, 2024)
The agrarian conflict in Rempang Island, Batam, centres on the construction of the Rempang Eco City National Strategic Project which requires the relocation of indigenous communities who have long lived there. This research aims to analyse indigenous peoples' resistance to the dispossession of customary land caused by the project, which threatens their existence. This research uses a qualitative approach with a literature study and secondary data analysis from online media coverage. Data was collected through NCapture with the keyword "Rempang" and analysed using NVivo12 Plus to understand the forms of resistance that emerged in the online media coverage. The results showed that the resistance of the Rempang indigenous community to the Rempang Eco City project arose due to development policies that did not involve them, threatening their existence. This resistance was triggered by the fear of losing customary land. Meanwhile, online media coverage highlighted the conflict between the community, security forces, and the project. From the results of content analysis, open forms of resistance actions such as "confrontation and sabotage" and closed forms of action such as "symbolic protests", as a response to perceived injustice. From the results of the narrative analysis, online media coverage tends to focus on social conflict and economic impacts, using words such as "Rempang," "residents," and "government." This research reveals the social dynamics and community responses to the controversial project on Rempang Island